Syncretism, Contextualization, Orthodoxy, and Heresy - Heideman, Eugene S. (Missiology, 1997)
Syncretism and contextualization are often heard by Third World and marginalized Christians as code words of power designed to maintain the traditional authority of missionaries and leaders of Western Christianity, with its roots in the trinitarian dogma established in the fourth century. In our times, when the Christian faith has to be thought out and lived in many non-Western cultures, it is important to focus more carefully on the second and third centuries, when the Christian apologists defended their faith and sought means to formulate liturgical and theological language in an age of pluralism, syncretism, and ritualism.